Element positioning doped lithium-rich manganese-based layered oxide and analysis method thereof
By accurately controlling the ion diffusion kinetics and doping element distribution, elemental positioning doping of lithium-rich manganese-based positive electrode materials is achieved, which solves the problem of insufficient performance of existing materials, improves electrochemical performance and stability, and is suitable for industrial production.
Patent Information
- Application Number
- CN202411673446.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-25
AI Technical Summary
The existing lithium-rich manganese-based positive electrode materials have problems such as low efficiency in the first circle of Coulomb, serious capacity and voltage attenuation, poor rate performance, and serious gas production, which limits its industrial application.
The ion diffusion kinetics are accurately controlled through parameters such as temperature and doping concentration, and the migration and distribution of doped elements in different atomic layers are adjusted. The method of insulation temperature combined with cooling rate is used to achieve the metastable state of doped elements distributed in different atomic layers. Control to prepare lithium-rich manganese-based layered oxides with elemental positioning doping.
Improves the electrochemical performance of the material, improves capacity retention, average voltage and high temperature electrochemical stability, and provides an efficient industrial large-scale preparation solution.
Smart Images

Figure CN119503900A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of lithium-ion batteries, and specifically relates to an element-locally doped lithium-rich manganese-based layered oxide and a method for analyzing the same. Background Art
[0002] At present, the cathode materials of commercial lithium-ion batteries mainly include lithium cobalt oxide, nickel-cobalt-manganese ternary materials, lithium iron phosphate, etc., and their specific capacities are mostly lower than 200mAh / g, which restricts the energy density of lithium-ion batteries and affects the development of high-energy lithium-ion battery application scenarios (such as long-range electric vehicles, drones, electric aircraft, etc.). The reversible specific capacity of lithium-manganese-based tetrafluoroethylene cathode materials (xLi2MnO3·(1-x)LiTMO2, TM=Ni, Mn, Co) is high and the cost is low, which is the key solution for realizing the cathode materials of high-energy lithium-ion batteries. However, lithium-manganese-based cathode materials still have many problems, including low first-cycle coulomb efficiency, severe capacity and voltage attenuation, poor rate performance, severe gas production, etc., which restrict their industrial application.
[0003] To solve the above problems, researchers have proposed a series of material modification schemes, such as element doping, surface coating, morphology control, composite materials, etc. Among them, element doping can change the local atomic structure of lithium-rich manganese-based cathode materials, thereby regulating electrochemical reactions and improving electrochemical performance. In addition, element doping has the advantages of small dosage, low cost, and easy amplification, which is suitable for industrial large-scale preparation of lithium-rich manganese-based cathode materials. However, many doping elements such as Al and Mg can occupy the lithium layer and transition metal layer of lithium-rich manganese-based layered oxides at the same time, and play different roles in different atomic layers. For example, when Mg is doped in the transition metal layer, it may form a Li-O-Mg configuration similar to Li-O-Li, which affects the electrochemical activity of oxygen anions; and when Mg is doped in the lithium layer, due to the strong Mg-O bond, it can play a pillaring role and stabilize the material structure when it is de-lithiated. It can be seen that regulating the occupancy ratio of doping elements in different atomic layers can effectively regulate the electrochemical properties of lithium-rich manganese-based cathode materials. However, this element-targeted doping strategy still faces great challenges, mainly including: (1) It is very difficult to effectively control the occupancy of doping elements in different atomic layers. This is because the occupancy of doping elements mainly depends on their intrinsic physical and chemical properties such as ionic radius and element valence state, and it is difficult to control these properties through external factors; (2) There is a lack of methods to quantitatively analyze the occupancy ratio of doping elements in different atomic layers. Currently, commonly used element occupancy analysis methods such as atomic resolution transmission electron microscopy can only provide local information, and it is difficult to obtain the occupancy ratio of doping elements in different atomic layers from an average and macroscopic perspective.
[0004] In view of this, the present invention provides an element-positioned doped lithium-rich manganese-based structured oxide and an analysis method thereof. The core of the present invention is to precisely control the ion diffusion dynamics through parameters such as temperature and doping concentration, adjust the migration and distribution of doping elements in different atomic layers, and achieve metastable regulation of lithium-rich manganese-based oxides with doping elements distributed in different atomic layers through the combination of insulation temperature and cooling rate, thereby preparing element-positioned doped lithium-rich manganese-based structured oxides. Summary of the invention
[0005] The present invention provides an element-positioned doped lithium-rich manganese-based layered oxide, wherein the lithium-rich manganese-based layered oxide contains one or more doping elements, and the doping elements occupy positions in the lithium layer and the transition metal layer of the lithium-rich manganese-based layered oxide, respectively, and the doping position ratio of the lithium layer and the transition metal layer is 5%-95%. The purpose of the present invention is to regulate the local atomic configuration of the lithium-rich manganese-based layered oxide, finely coordinate the different physical and chemical effects caused by the different positions of the doping elements, and thus improve the electrochemical properties of the material.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] An element-positioned doped lithium-rich manganese-based structured oxide is prepared by a coprecipitation method or a solid phase sintering method. The element-positioned doping is simultaneously achieved when preparing the lithium-rich manganese-based structured oxide. The specific technical solution includes the following steps:
[0008] Step (1): a raw material containing a transition metal element and a raw material containing a doping element are subjected to a coprecipitation reaction to form a lithium-rich manganese-based layered oxide precursor in which the transition metal element is uniformly distributed, or the raw material containing a transition metal element and the raw material containing a doping element are fully mixed by a ball milling method to form a uniformly distributed mixture;
[0009] Specifically, when the coprecipitation method is used, a solution of a doping element raw material is simultaneously added to a salt solution containing a transition metal element, and a lithium-rich manganese-based layered oxide precursor having an atomic / nanoscale element uniformly distributed therein is formed by a coprecipitation reaction;
[0010] Specifically, when the direct solid phase sintering method is used, the raw material containing the transition metal element and the raw material containing the doping element are ball-milled and fully mixed to form a mixture in which the transition metal element and the doping element are uniformly distributed;
[0011] Step (2): the lithium-rich manganese-based layered oxide precursor obtained by the coprecipitation method in step (1) or the mixture of transition metal elements and doping elements uniformly distributed obtained by the ball milling method is fully mixed with a lithium source, followed by high-temperature sintering, and the temperature and atmosphere during the sintering process are precisely controlled to control the kinetics and thermodynamics of the doping elements during the sintering process, thereby precisely controlling the position of the doping elements in the lithium layer and the transition metal layer, and obtaining an element-positioned doped lithium-rich manganese-based layered oxide after cooling.
[0012] Specifically, when the coprecipitation method is used, a lithium-rich manganese-based layered oxide precursor is fully mixed with a lithium source;
[0013] Specifically, when the direct solid phase sintering method is adopted, the lithium-rich manganese-based layered oxide raw material and the doping element raw material are fully mixed by adding the lithium source during or after ball milling;
[0014] In the preparation method, the lithium-rich manganese-based layered oxide raw material includes one or more of manganese salts, nickel salts and cobalt salts, wherein the manganese salts include but are not limited to one or more of manganese sulfate, manganese nitrate, manganese acetate and hydrates thereof, the nickel salts include but are not limited to one or more of nickel sulfate, nickel nitrate, nickel acetate and hydrates thereof, and the cobalt salts include but are not limited to one or more of cobalt sulfate, cobalt nitrate, cobalt acetate and hydrates thereof. Manganese acetate tetrahydrate, nickel acetate tetrahydrate and cobalt acetate tetrahydrate are preferred.
[0015] In the preparation method, the lithium raw material includes but is not limited to one or more of lithium carbonate, lithium hydroxide, lithium sulfate, lithium nitrate and lithium acetate, preferably lithium hydroxide monohydrate. The excess lithium content is 0%-25%, preferably 5%.
[0016] In the preparation method, the doping elements include but are not limited to one or more of Al, Mg, Ca, Na, K and Ti, preferably Al and Mg. The total doping amount of the doping elements is between 0.1% and 10.0%, preferably 2% to 5%.
[0017] In the preparation method, the doping element raw material includes but is not limited to one or more of sulfate, nitrate of the doping element, acetate of the doping element and hydrates thereof, preferably acetate.
[0018] In the preparation method, high-temperature sintering adopts a one-step sintering method or a multi-step sintering method, preferably a two-step sintering method; the sintering atmosphere includes but is not limited to air, O2, O2 / N2 mixed gas or O2 / Ar mixed gas, preferably air; the heating rate is 1-10°C / min, preferably 2°C / min; the sintering temperature is 450-1000°C, and the total insulation time is 2-48h, preferably two-step sintering, the first step sintering temperature is 500°C, insulation time is 5h, the second step sintering temperature is 900°C, insulation time is 10h.
[0019] The present invention also provides a quantitative analysis method for element-localized doping of lithium-rich manganese-based layered oxides, the steps of which include:
[0020] Step (1): Positioning and doping the element into the lithium-rich manganese-based layered oxide, performing ND analysis sensitive to the lithium element, and obtaining average crystal structure information; and performing structural refinement on the ND test results to quantitatively analyze the occupancy information of lithium ions in the lithium layer and transition metal layer of the lithium-rich manganese-based layered oxide;
[0021] Step (2): Positioning the doping of elements into the lithium-rich manganese-based layered oxide, performing XRD analysis, and obtaining the average crystal structure information of the material; performing structural refinement on the results, and eliminating the interference of lithium ions on the occupancy of doped ions on the basis of ND quantitative analysis of the occupancy information of lithium ions, thereby quantitatively analyzing the proportion of doped elements in the lithium layer and transition metal layer of the lithium-rich manganese-based layered oxide.
[0022] The beneficial effects of the present invention include: finely coordinating the position of doping elements in lithium-rich manganese-based layered oxides, adjusting the local atomic configuration and physicochemical effects of the material, and improving the electrochemical properties of the material. The obtained lithium-rich manganese-based layered oxide has the advantages of high capacity retention, reduced average voltage, and good high-temperature electrochemical stability. In addition, the quantitative analysis method of element positioning doping provided by the present invention has the advantages of simple sample preparation, high accuracy, and process flow, and is a key method for quantitatively analyzing the position of doping elements in lithium-rich manganese-based layered oxides from the perspective of average and macro. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The figure is a comparison of the cycle performance of the batteries of Example 1 and Comparative Example 1 at 25°C;
[0024] Figure 2 The figure shows the cycle performance comparison of the batteries of Example 2 and Comparative Example 1 at 55°C. DETAILED DESCRIPTION
[0025] Example 1
[0026] (1) Mn(CH3COO)2·4H2O, Ni(CH3COO)2·4H2O, Co(CH3COO)2·4H2O and Al(NO)3·9H2O were mixed in a molar ratio of 0.516:0.167:0.067:0.05, added to a ball mill in air, with a ball-to-material ratio of 10:1, and ball milled at a speed of 200 rpm for 4 h. Then, LiOH·H2O with an excess lithium content of 5% was added to the resulting mixture, and the mixture was further ball milled at a speed of 200 rpm for 10 h. The mixture was collected and fully dried in a vacuum drying oven. The resulting mixture was added to a sintering furnace in air, heated to 500°C at a heating rate of 2°C / min, and sintered at 500°C for 5 h. Then, it was heated to 900°C at a heating rate of 2°C / min, and sintered at 900°C for 10 h. The material is naturally cooled to room temperature to obtain a lithium-rich manganese-based layered oxide doped with Al element, the average structure of which is Li 1.2 Mn 0.516 Al 0.05 Ni 0.167 Co 0.067 O2, the total Al element doping amount of which is 5%.
[0027] (2) The above materials were subjected to high-resolution powder neutron diffraction (ND) testing, where the sub-wavelength is High-resolution ND diffraction peaks were obtained; GSAS software was used for structural refinement to quantitatively analyze the occupancy information of lithium ions in the lithium layer and transition metal layer of lithium-rich manganese-based layered oxides; the above materials were then subjected to synchrotron radiation powder X-ray diffraction (XRD) testing, and the X-ray wavelength was High-resolution XRD diffraction peaks were obtained; GSAS software was used for structural refinement to fix the occupancy information of lithium ions in the lithium layer and transition metal layer of the lithium-rich manganese-based hierarchical oxide, thereby analyzing that the occupancy ratios of the Al element in the lithium layer and transition metal layer of the lithium-rich manganese-based hierarchical oxide are 0.7(1)% and 4.3(1)%, respectively.
[0028] (3) The obtained Al-doped lithium-rich manganese-based layered oxide positive electrode material was subjected to electrochemical performance testing. The cycle performance was tested using a CR2032 button cell. The ratio of positive electrode material: conductive carbon (SP): binder (PVDF) in the button cell positive electrode plate was 8:1:1. A Celgard 2400 separator was used. A metal lithium sheet was used for the negative electrode. The electrolyte was a high-voltage electrolyte purchased from Guotai Huarong Company. The assembled battery was charged and discharged at 25°C and 2.0-4.8V for the first cycle at a current density of 5mA / g. Thereafter, the battery was charged and discharged at 25°C and 2.0-4.8V at a current density of 100mA / g. The capacity retention rate after 200 cycles was 91.3%, which was significantly better than that of the undoped lithium-rich layered oxide Li in Comparative Example 1.1.2 Mn 0.566 Ni 0.167 Co 0.067 The capacity retention rate of O2 under the same test conditions is 72.6%.
[0029] Embodiment 2:
[0030] (1) Mn(CH3COO)2·4H2O, Ni(CH3COO)2·4H2O, Co(CH3COO)2·4H2O and Mg(CH3COO)2·4H2O were mixed in a molar ratio of 0.516:0.167:0.067:0.05, added to a ball mill in air, with a ball-to-material ratio of 10:1, and ball milled at a speed of 200 rpm for 4 h. Then, LiOH·H2O with an excess lithium content of 5% was added to the resulting mixture, and the mixture was further ball milled at a speed of 200 rpm for 10 h. The mixture was collected and fully dried in a vacuum drying oven. The resulting mixture was added to a sintering furnace in air, heated to 500°C at a heating rate of 2°C / min, and sintered at 500°C for 5 h. Then, it was heated to 900°C at a heating rate of 2°C / min, and sintered at 900°C for 10 h. The material is naturally cooled to room temperature to obtain a lithium-rich manganese-based layered oxide doped with Mg element, the average structure of which is Li 1.2 Mn 0.516 Mg 0.05 Ni 0.167 Co 0.067 O2, the total Mg element doping amount of which is 5%.
[0031] (2) The above materials were subjected to high-resolution powder neutron diffraction (ND) testing, where the sub-wavelength is High-resolution ND diffraction peaks were obtained; GSAS software was used for structural refinement to quantitatively analyze the occupancy information of lithium ions in the lithium layer and transition metal layer of lithium-rich manganese-based layered oxides; the above materials were then subjected to synchrotron radiation powder X-ray diffraction (XRD) testing, and the X-ray wavelength was High-resolution XRD diffraction peaks were obtained; GSAS software was used for structural refinement to fix the occupancy information of lithium ions in the lithium layer and transition metal layer of the lithium-rich manganese-based hierarchical oxide, thereby analyzing that the occupancy ratios of the Mg element in the lithium layer and transition metal layer of the lithium-rich manganese-based hierarchical oxide are 2.2(2)% and 2.8(2)%, respectively.
[0032] (3) The electrochemical performance of the obtained Mg-doped lithium-rich manganese-based layered oxide positive electrode material was tested. The cycle performance was tested using a CR2032 button cell. The ratio of positive electrode material: conductive carbon (SP): binder (PVDF) in the button cell positive electrode plate was 8:1:1. A Celgard 2400 separator was used. A metal lithium sheet was used for the negative electrode. The electrolyte was a high-voltage electrolyte purchased from Guotai Huarong Company. The assembled battery was charged and discharged at 55°C and 2.0-4.8V for the first cycle at a current density of 5mA / g, and then charged and discharged at 55°C and 2.0-4.8V at a current density of 100mA / g. The capacity retention rate for 50 cycles was 100%, which was significantly better than that of the undoped lithium-rich layered oxide Li in Comparative Example 1. 1.2 Mn 0.566 Ni 0.167 Co 0.067 The capacity retention rate of O2 under the same test conditions is 73.5%.
[0033] Embodiment 3:
[0034] (1) Mn(CH3COO)2·4H2O, Ni(CH3COO)2·4H2O, Co(CH3COO)2·4H2O and Al(NO)3·9H2O, Mg(CH3COO)2·4H2O were mixed in a molar ratio of 0.526:0.167:0.067:0.02:0.02 and added to a ball mill in air. The ball-to-material ratio was fixed at 10:1 and the ball mill was milled at a speed of 200 rpm for 4 h. Thereafter, LiOH·H2O with an excess lithium content of 6% was added to the resulting mixture and the mixture was further milled at a speed of 250 rpm for 8 h. The mixture was collected and thoroughly dried in a vacuum drying oven. The resulting mixture was added to a sintering furnace in air, heated to 550°C at a heating rate of 2°C / min, and sintered at 550°C for 6 h. Then, the material was heated to 880°C at a heating rate of 2°C / min and sintered at 880°C for 12 hours. The material was naturally cooled to room temperature to obtain a lithium-rich manganese-based hierarchical oxide doped with Al / Mg elements, with an average structure of Li 1.2 Mn 0.526 Al 0.02 Mg 0.02 Ni 0.167 Co 0.067 O2, the total doping amount of Al and Mg elements is 4%.
[0035] (2) The above materials were subjected to high-resolution powder neutron diffraction (ND) testing, where the sub-wavelength is High-resolution ND diffraction peaks were obtained; GSAS software was used for structural refinement to quantitatively analyze the occupancy information of lithium ions in the lithium layer and transition metal layer of lithium-rich manganese-based layered oxides; the above materials were then subjected to synchrotron radiation powder X-ray diffraction (XRD) testing, and the X-ray wavelength was High-resolution XRD diffraction peaks were obtained; GSAS software was used for structural refinement to fix the occupancy information of lithium ions in the lithium layer and transition metal layer of the lithium-rich manganese-based hierarchical oxide, thereby analyzing that the occupancy ratios of the Al element in the lithium layer and transition metal layer of the lithium-rich manganese-based hierarchical oxide were 0.3(1)% and 1.7(1)%, respectively; and the occupancy ratios of the Mg element in the lithium layer and transition metal layer of the lithium-rich manganese-based hierarchical oxide were 0.9(2)% and 1.1(2)%, respectively.
[0036] (3) The obtained Al / Mg element doped lithium-rich manganese-based layered oxide positive electrode material was subjected to electrochemical performance testing. The cycle performance was tested using a CR2032 button cell. The ratio of positive electrode material: conductive carbon (SP): binder (PVDF) in the button cell positive electrode plate was 8:1:1. A Celgard 2400 separator was used. A metal lithium sheet was used for the negative electrode. The electrolyte was a high-voltage electrolyte purchased from Guotai Huarong Company. The assembled battery was charged and discharged at 25°C and 2.0-4.8V for the first cycle at a current density of 5mA / g. Thereafter, the battery was charged and discharged at 25°C and 2.0-4.8V at a current density of 100mA / g. The capacity retention rate after 200 cycles was 92.4%, which was significantly better than that of the undoped lithium-rich layered oxide Li in Comparative Example 1. 1.2 Mn 0.566 Ni 0.167 Co 0.067 The capacity retention rate of O2 under the same test conditions is 72.6%.
[0037] Embodiment 4:
[0038] (1) Mn(CH3COO)2·4H2O, Ni(CH3COO)2·4H2O and Al(NO)3·9H2O were mixed in a molar ratio of 0.516:0.233:0.05 and added to a ball mill in air. The ball-to-material ratio was fixed at 10:1 and the mixture was ball milled at a speed of 200 rpm for 4 hours. Thereafter, LiOH·H2O with an excess lithium content of 5% was added to the mixture and the mixture was further ball milled at a speed of 200 rpm for 10 hours. The mixture was collected and thoroughly dried in a vacuum drying oven. The mixture was added to a sintering furnace in air, heated to 500°C at a heating rate of 2°C / min, and sintered at 500°C for 5 hours. Thereafter, the mixture was heated to 900°C at a heating rate of 2°C / min and sintered at 900°C for 10 hours. The material was naturally cooled to room temperature to obtain a cobalt-free lithium-rich manganese-based hierarchical oxide doped with Al element, the average structure of which is Li 1.2 Mn 0.516 Al 0.05 Ni 0.233 O2, the total Al element doping amount of which is 5%.
[0039] (2) The above materials were subjected to high-resolution powder neutron diffraction (ND) testing, where the sub-wavelength is High-resolution ND diffraction peaks were obtained; GSAS software was used for structural refinement to quantitatively analyze the occupancy information of lithium ions in the lithium layer and transition metal layer of lithium-rich manganese-based layered oxides; the above materials were then subjected to synchrotron radiation powder X-ray diffraction (XRD) testing, and the X-ray wavelength was High-resolution XRD diffraction peaks were obtained; GSAS software was used for structural refinement to fix the occupancy information of lithium ions in the lithium layer and transition metal layer of the lithium-rich manganese-based hierarchical oxide, thereby analyzing that the occupancy ratios of the Al element in the lithium layer and transition metal layer of the lithium-rich manganese-based hierarchical oxide are 0.8(1)% and 4.2(1)%, respectively.
[0040] (3) The obtained Al-doped cobalt-free lithium-rich manganese-based hierarchical oxide positive electrode material was tested for electrochemical performance. The cycle performance was tested using a CR2032 button cell. The ratio of positive electrode material: conductive carbon (SP): binder (PVDF) in the button cell positive electrode plate was 8:1:1. A Celgard 2400 separator was used. A metal lithium sheet was used for the negative electrode. The electrolyte was a high-voltage electrolyte purchased from Guotai Huarong Company. The assembled battery was charged and discharged at 25°C, 2.0-4.8V, with a current density of 5mA / g for the first cycle. Then, the battery was charged and discharged at 25°C, 2.0-4.8V, with a current density of 100mA / g. The capacity retention rate after 200 cycles was 90.1%.
[0041] Embodiment 5:
[0042] (1) Mn(CH3COO)2·4H2O, Ni(CH3COO)2·4H2O, Co(CH3COO)2·4H2O and Al(NO)3·9H2O were dissolved in deionized water at a molar ratio of 0.536:0.167:0.067:0.03; a Na2CO3 solution with a concentration of 2 mol / L was prepared as a precipitant; an ammonia solution with a concentration of 0.4 mol / L was prepared as a complexing agent; the solution was added to a coprecipitation reactor through a peristaltic pump for stirring, and an alkali solution and a complexing agent solution were added to the reactor through a peristaltic pump in parallel, the reaction temperature was controlled at 55°C, the pH was maintained at 7.7, the stirring speed was 1000 rpm / min, N2 was used as an inert gas to protect the coprecipitation reaction during the entire reaction process, and after the coprecipitation reaction was carried out for 30 hours, a carbonate precursor material of lithium-rich layered oxide containing nickel, manganese and cobalt was obtained. The obtained mixture was added into a sintering furnace in air, heated to 500°C at a heating rate of 2°C / min, and sintered at 500°C for 5 hours. Then, the mixture was heated to 900°C at a heating rate of 2°C / min, and sintered at 900°C for 10 hours. The material was naturally cooled to room temperature to obtain a lithium-rich manganese-based hierarchical oxide doped with Al element, with an average structure of Li 1.2 Mn 0.536 Al 0.03 Ni 0.167 Co 0.067 O2, the total Al element doping amount of which is 3%.
[0043] (2) The above materials were subjected to high-resolution powder neutron diffraction (ND) testing, where the sub-wavelength is High-resolution ND diffraction peaks were obtained; GSAS software was used for structural refinement to quantitatively analyze the occupancy information of lithium ions in the lithium layer and transition metal layer of lithium-rich manganese-based layered oxides; the above materials were then subjected to synchrotron radiation powder X-ray diffraction (XRD) testing, and the X-ray wavelength was High-resolution XRD diffraction peaks were obtained; GSAS software was used for structural refinement to fix the occupancy information of lithium ions in the lithium layer and transition metal layer of the lithium-rich manganese-based hierarchical oxide, thereby analyzing that the occupancy ratios of the Al element in the lithium layer and transition metal layer of the lithium-rich manganese-based hierarchical oxide are 0.5(1)% and 2.5(1)%, respectively.
[0044] (3) The electrochemical performance of the obtained Al-doped lithium-rich manganese-based layered oxide positive electrode material was tested. The cycle performance was tested using a CR2032 button cell. The ratio of positive electrode material: conductive carbon (SP): binder (PVDF) in the button cell positive electrode plate was 8:1:1. A Celgard 2400 separator was used. A metal lithium sheet was used for the negative electrode. The electrolyte was a high-voltage electrolyte purchased from Guotai Huarong Company. The assembled battery was charged and discharged at 25°C and 2.0-4.8V for the first cycle at a current density of 5mA / g. Thereafter, the battery was charged and discharged at 25°C and 2.0-4.8V at a current density of 100mA / g. The capacity retention rate after 200 cycles was 90.8%, which was significantly better than that of the undoped lithium-rich layered oxide Li in Comparative Example 2. 1.2 Mn 0.566 Ni 0.167 Co 0.067 The capacity retention rate of O2 under the same test conditions is 74.3%.
[0045] Embodiment 6:
[0046] (1) Mn(CH3COO)2·4H2O, Ni(CH3COO)2·4H2O, Co(CH3COO)2·4H2O and Mg(CH3COO)2·4H2O were dissolved in deionized water at a molar ratio of 0.537:0.167:0.067:0.03; a Na2CO3 solution with a concentration of 2 mol / L was prepared as a precipitant; an ammonia solution with a concentration of 0.4 mol / L was prepared as a complexing agent; the solution was added to a coprecipitation reactor through a peristaltic pump for stirring, and an alkali solution and a complexing agent solution were added to the reactor through a peristaltic pump in parallel, the reaction temperature was controlled at 55°C, the pH was maintained at 7.7, the stirring speed was 900 rpm / min, N2 was used as an inert gas to protect the coprecipitation reaction during the entire reaction process, and after the coprecipitation reaction was carried out for 26 hours, a carbonate precursor material of lithium-rich layered oxide containing nickel, manganese and cobalt was obtained. The obtained mixture was added into a sintering furnace in air, heated to 550°C at a heating rate of 1°C / min, and sintered at 550°C for 4 hours. Then, it was heated to 850°C at a heating rate of 1°C / min, and sintered at 850°C for 12 hours. The material was naturally cooled to room temperature to obtain a lithium-rich manganese-based hierarchical oxide doped with Mg element, and its average structure was Li 1.2 Mn 0.537 Mg 0.03 Ni 0.167 Co 0.067 O2, the total Mg element doping amount of which is 3%.
[0047] (2) The above materials were subjected to high-resolution powder neutron diffraction (ND) testing, where the sub-wavelength is High-resolution ND diffraction peaks were obtained; GSAS software was used for structural refinement to quantitatively analyze the occupancy information of lithium ions in the lithium layer and transition metal layer of lithium-rich manganese-based layered oxides; the above materials were then subjected to synchrotron radiation powder X-ray diffraction (XRD) testing, and the X-ray wavelength was High-resolution XRD diffraction peaks were obtained; GSAS software was used for structural refinement to fix the occupancy information of lithium ions in the lithium layer and transition metal layer of the lithium-rich manganese-based hierarchical oxide, thereby analyzing that the occupancy ratios of the Mg element in the lithium layer and transition metal layer of the lithium-rich manganese-based hierarchical oxide are 1.2(1)% and 1.8(1)%, respectively.
[0048] (3) The electrochemical performance of the obtained Mg-doped lithium-rich manganese-based layered oxide positive electrode material was tested. The cycle performance was tested using a CR2032 button cell. The ratio of positive electrode material: conductive carbon (SP): binder (PVDF) in the button cell positive electrode plate was 8:1:1. A Celgard 2400 separator was used. A metal lithium sheet was used for the negative electrode. The electrolyte was a high-voltage electrolyte purchased from Guotai Huarong Company. The assembled battery was charged and discharged at 55°C and 2.0-4.8V for the first cycle at a current density of 5mA / g. Thereafter, the battery was charged and discharged at 55°C and 2.0-4.8V at a current density of 100mA / g. The capacity retention rate after 200 cycles was 97.2%, which was significantly better than that of the undoped lithium-rich layered oxide Li in Comparative Example 2. 1.2 Mn 0.567 Ni 0.167 Co 0.067 The capacity retention rate of O2 under the same test conditions is 71.7%.
[0049] Embodiment 7:
[0050] (1) Mn(CH3COO)2·4H2O, Ni(CH3COO)2·4H2O, Co(CH3COO)2·4H2O and Ti(NO3)4 were dissolved in deionized water at a molar ratio of 0.516:0.167:0.067:0.05; a Na2CO3 solution with a concentration of 2 mol / L was prepared as a precipitant; an ammonia solution with a concentration of 0.4 mol / L was prepared as a complexing agent; the solution was added to a coprecipitation reactor through a peristaltic pump for stirring, and an alkali solution and a complexing agent solution were added to the reactor through a peristaltic pump in parallel, the reaction temperature was controlled at 55°C, the pH was maintained at 7.7, the stirring speed was 900 rpm / min, N2 was used as an inert gas to protect the coprecipitation reaction during the entire reaction process, and after the coprecipitation reaction was carried out for 26 hours, a carbonate precursor material of lithium-rich layered oxide containing nickel, manganese and cobalt was obtained. The obtained mixture was added into a sintering furnace in air, heated to 550°C at a heating rate of 1°C / min, and sintered at 550°C for 4 hours. Then, it was heated to 850°C at a heating rate of 1°C / min, and sintered at 850°C for 12 hours. The material was naturally cooled to room temperature to obtain a lithium-rich manganese-based hierarchical oxide doped with Mg element, and its average structure was Li 1.2 Mn 0.517 Ti 0.05 Ni 0.167 Co 0.067 O2, the total doping amount of Ti element is 5%.
[0051] (2) The above materials were subjected to high-resolution powder neutron diffraction (ND) testing, where the sub-wavelength is High-resolution ND diffraction peaks were obtained; GSAS software was used for structural refinement to quantitatively analyze the occupancy information of lithium ions in the lithium layer and transition metal layer of lithium-rich manganese-based layered oxides; the above materials were then subjected to synchrotron radiation powder X-ray diffraction (XRD) testing, and the X-ray wavelength was High-resolution XRD diffraction peaks were obtained; GSAS software was used for structural refinement to fix the occupancy information of lithium ions in the lithium layer and transition metal layer of the lithium-rich manganese-based hierarchical oxide, thereby analyzing that the occupancy ratios of the Ti element in the lithium layer and transition metal layer of the lithium-rich manganese-based hierarchical oxide are 1.8(1)% and 3.2(1)%, respectively.
[0052] (3) The obtained Ti element doped lithium-rich manganese-based layered oxide positive electrode material was subjected to electrochemical performance testing. The cycle performance was tested using a CR2032 button cell. The ratio of positive electrode material: conductive carbon (SP): binder (PVDF) in the button cell positive electrode plate was 8:1:1. A Celgard 2400 separator was used. A metal lithium sheet was used for the negative electrode. The electrolyte was a high-voltage electrolyte purchased from Guotai Huarong Company. The assembled battery was charged and discharged at 25°C and 2.0-4.8V for the first cycle at a current density of 5mA / g. Thereafter, the battery was charged and discharged at 25°C and 2.0-4.8V at a current density of 100mA / g. The capacity retention rate after 200 cycles was 88.4%, which was significantly better than that of the undoped lithium-rich layered oxide Li in Comparative Example 2. 1.2 Mn 0.567 Ni 0.167 Co 0.067 The capacity retention rate of O2 under the same test conditions is 74.3%.
[0053] Comparative Example 1:
[0054] (1) Mn(CH3COO)2·4H2O, Ni(CH3COO)2·4H2O and Co(CH3COO)2·4H2O were mixed in a molar ratio of 0.566:0.167:0.067 and added to a ball mill in air. The ball-to-material ratio was fixed at 10:1 and the ball mill was milled at a speed of 200 rpm for 4 hours. Thereafter, LiOH·H2O with an excess lithium content of 5% was added to the resulting mixture and the mixture was further milled at a speed of 200 rpm for 10 hours. The mixture was collected and thoroughly dried in a vacuum drying oven. The resulting mixture was added to a sintering furnace in air, heated to 500°C at a heating rate of 2°C / min, and sintered at 500°C for 5 hours. Thereafter, the mixture was heated to 900°C at a heating rate of 2°C / min and sintered at 900°C for 10 hours. The material was naturally cooled to room temperature to obtain an undoped lithium-rich manganese-based hierarchical oxide with an average structure of Li 1.2 Mn 0.566 Ni 0.167 Co 0.067 O2.
[0055] (2) The obtained undoped lithium-rich manganese-based hierarchical oxide positive electrode material was subjected to electrochemical performance testing, and the cycle performance was tested using a CR2032 button cell. The ratio of positive electrode material: conductive carbon (SP): binder (PVDF) in the button cell positive electrode plate was 8:1:1, Celgard 2400 type diaphragm was used, metal lithium sheet was used for the negative electrode, and the electrolyte was a high-voltage electrolyte purchased from Guotai Huarong Company. The assembled battery was charged and discharged at 25°C, 2.0-4.8V at a current density of 5mA / g for the first cycle, and then charged and discharged at 25°C, 2.0-4.8V at a current density of 100mA / g. The capacity retention rate after 200 cycles was 72.6%. The assembled battery was charged and discharged for the first cycle at 55°C, 2.0-4.8V with a current density of 5mA / g, and then charged and discharged at 55°C, 2.0-4.8V with a current density of 100mA / g. The capacity retention rate was 73.5% after 50 cycles.
[0056] Comparative Example 2:
[0057] (1) Mn(CH3COO)2·4H2O, Ni(CH3COO)2·4H2O and Co(CH3COO)2·4H2O were dissolved in deionized water at a molar ratio of 0.566:0.167:0.067; a Na2CO3 solution with a concentration of 2 mol / L was prepared as a precipitant; an ammonia solution with a concentration of 0.4 mol / L was prepared as a complexing agent; the solution was added to a coprecipitation reactor through a peristaltic pump for stirring, and an alkali solution and a complexing agent solution were added to the reactor through a peristaltic pump in parallel, the reaction temperature was controlled at 55°C, the pH was maintained at 7.7, the stirring speed was 900 rpm / min, N2 was used as an inert gas to protect the coprecipitation reaction during the entire reaction process, and after the coprecipitation reaction was carried out for 26 hours, a carbonate precursor material of lithium-rich layered oxide containing nickel, manganese and cobalt was obtained. The obtained mixture was added to a sintering furnace in air, heated to 550°C at a heating rate of 1°C / min, and sintered at 550°C for 4 hours. Then, it was heated to 850°C at a heating rate of 1°C / min, and sintered at 850°C for 12 hours. The material was naturally cooled to room temperature, i.e., an undoped lithium-rich manganese-based hierarchical oxide with an average structure of Li 1.2 Mn 0.566 Ni 0.167 Co 0.067 O2.
[0058] (2) The obtained undoped lithium-rich manganese-based layered oxide positive electrode material was subjected to electrochemical performance testing, and the cycle performance was tested using a CR2032 button cell. The ratio of positive electrode material: conductive carbon (SP): binder (PVDF) in the button cell positive electrode plate was 8:1:1, Celgard 2400 type diaphragm was used, metal lithium sheet was used for the negative electrode, and the electrolyte was a high-voltage electrolyte purchased from Guotai Huarong Company. The assembled battery was charged and discharged at 25°C, 2.0-4.8V at a current density of 5mA / g for the first cycle, and then charged and discharged at 25°C, 2.0-4.8V at a current density of 100mA / g. The capacity retention rate after 200 cycles was 74.3%. The assembled battery was charged and discharged for the first cycle at 55°C, 2.0-4.8V with a current density of 5mA / g, and then charged and discharged at 55°C, 2.0-4.8V with a current density of 100mA / g. The capacity retention rate was 71.7% after 50 cycles.
[0059] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. An element-directed doped lithium-rich manganese-based layered oxide, characterized in that: The lithium-rich manganese-based layered oxide contains one or more doping elements, which respectively occupy the lithium layer and the transition metal layer of the lithium-rich manganese-based layered oxide, and the doping elements occupy 5%-95% of the lithium layer and the transition metal layer.
2. The element-locally doped lithium-rich manganese-based layered oxide according to claim 1, characterized in that: The doping elements include but are not limited to one or more of Al, Mg, Ca, Na, K and Ti, and the total doping amount of the doping elements is between 0.1% and 10.0%.
3. The method for preparing the element-directed doped lithium-rich manganese-based layered oxide according to claim 1 or 2, characterized in that: The lithium-rich manganese-based layered oxide is prepared by a coprecipitation method or a solid phase sintering method.
4. The method for preparing an element-directed doped lithium-rich manganese-based layered oxide according to claim 3, characterized in that: The element-localized doping is realized simultaneously when preparing the lithium-rich manganese-based layered oxide, and includes the following steps: (1) forming a lithium-rich manganese-based layered oxide precursor in which the transition metal element is uniformly distributed by coprecipitation reaction of a raw material containing a transition metal element and a raw material containing a doping element, or fully mixing the raw material containing a transition metal element and a raw material containing a doping element by ball milling to form a uniformly distributed mixture; When the coprecipitation method is used, a solution of a doping element raw material is simultaneously added to a salt solution containing a transition metal element, and a lithium-rich manganese-based layered oxide precursor having an atomic / nanoscale element uniformly distributed therein is formed by a coprecipitation reaction; When the direct solid phase sintering method is used, the raw material containing the transition metal element and the raw material of the doping element are ball-milled and fully mixed to form a mixture in which the transition metal element and the doping element are evenly distributed; (2) the lithium-rich manganese-based layered oxide precursor obtained by the coprecipitation method in (1) or the mixture of transition metal elements and doping elements uniformly distributed obtained by the ball milling method is fully mixed with a lithium source, followed by high-temperature sintering, and the kinetics and thermodynamics of the doping elements during the sintering process are controlled by precisely controlling the temperature and atmosphere during the sintering process, thereby precisely controlling the position of the doping elements in the lithium layer and the transition metal layer, and obtaining the element-positioned doped lithium-rich manganese-based layered oxide after cooling; When the co-precipitation method is used, the lithium-rich manganese-based layered oxide precursor is thoroughly mixed with a lithium source; When the direct solid phase sintering method is adopted, the lithium source is added to the lithium-rich manganese-based layered oxide raw material and the doping element raw material during or after ball milling and the mixture is fully mixed.
5. The method for preparing an element-locally doped lithium-rich manganese-based layered oxide according to claim 4, characterized in that: The raw materials containing transition metal elements include one or more of manganese salts, nickel salts and cobalt salts; the manganese salts include but are not limited to one or more of manganese sulfate, manganese nitrate, manganese acetate and hydrates thereof; the nickel salts include but are not limited to one or more of nickel sulfate, nickel nitrate, nickel acetate and hydrates thereof; the cobalt salts include but are not limited to one or more of cobalt sulfate, cobalt nitrate, cobalt acetate and hydrates thereof.
6. The method for preparing an element-locally doped lithium-rich manganese-based layered oxide according to claim 4, characterized in that: The lithium raw material includes but is not limited to one or more of lithium carbonate, lithium hydroxide, lithium sulfate, lithium nitrate and lithium acetate, and the excess lithium content is 0%-25%.
7. The method for preparing an element-locally doped lithium-rich manganese-based layered oxide according to claim 4, characterized in that: The doping element raw material includes, but is not limited to, one or more of sulfates of the doping element, nitrates of the doping element, acetates of the doping element, and hydrates thereof.
8. The method for preparing an element-directed doped lithium-rich manganese-based layered oxide according to claim 4, characterized in that: The high temperature sintering adopts a one-step sintering method or a multi-step sintering method. The sintering atmosphere includes but is not limited to air, O2, O2 / N2 mixed gas or O2 / Ar mixed gas. The heating rate is 1-10°C / min, the sintering temperature is 450-1000°C, and the total insulation time is 2-48h.
9. A quantitative analysis method for element-directed doping of lithium-rich manganese-based layered oxides, the steps comprising: (1) performing a neutron diffraction analysis sensitive to lithium on the lithium-rich manganese-based layered oxide doped with any one of the elements described in 1 to 2 or the lithium-rich manganese-based layered oxide prepared by the preparation method described in any one of claims 3 to 8, and obtaining average crystal structure information; and performing Rietveld structure refinement on the ND test results, and quantitatively analyzing the occupancy information of lithium ions in the lithium layer and transition metal layer of the lithium-rich manganese-based layered oxide; (2) performing X-ray diffraction analysis on the lithium-rich manganese-based layered oxide doped with an element as described in any one of 1 to 2 or the lithium-rich manganese-based layered oxide prepared by the preparation method described in any one of claims 3 to 8 to obtain the average crystal structure information of the material; performing structural refinement on the result, and on the basis of the ND quantitative analysis of the occupancy information of lithium ions, eliminating the interference of lithium ions on the occupancy of doped ions, thereby quantitatively analyzing the proportion of the doping element in the lithium layer and the transition metal layer of the lithium-rich manganese-based layered oxide.
10. A lithium ion battery, characterized in that: The lithium-ion battery uses any element-doped lithium-rich manganese-based layered oxide as described in 1 to 2 or an element-doped lithium-rich manganese-based layered oxide prepared by the preparation method described in any one of claims 3 to 8 as the positive electrode material.